Pollen on the Shroud of Turin: The Probable Trace Left by Anointing and Embalming. (28th October 2016) - Boi, M.
Abstract : This study proposes an alternative interpretation of the pollen grains found on the Christian relic of the Shroud of Turin, the majority of which belong to entomogamous plants. The examination of the images in the literature and the observation of modern pollen under light microscopy and scanning electron microscopy reveal that the most abundant pollen on the relic may be attributed to the genus Helichrysum (Asteraceae family) instead of Gundelia tournefortii. The other most important pollen found belongs to the Cistaceae‐Cistus spp.—the Apiaceae—probably Ferula spp.—and the Anacardianceae—the genus Pistacia. These pollen grains could have come from plants used to obtain expensive and valuable substances that would have been the basis for the oils of Helichrysum, ladanum and galbanum, as well as for mastic and terebinth products; this fact has not been considered by previous authors. Ancient historical records give us references that could link the pollen traces to a mixture of balms and ointments employed for preparing the body for funeral and burial. For this reason, the palynological study reveals coherency with these historical records about the rituals, as reported on by the important scientists Pliny the Elder and Dioscorides, dating back to the first centuryad .